Creating Eco-Innovations for Sustainable Entrepreneurship and Development within European Countries - Prokop, Viktor; Stejskal, Jan; Hajek, Petr; Kuba, Ondrej (European Journal of Sustainable Development, 2019)
There is no doubt that innovations represented key source of competitive advantage in the last years. Therefore, firms were forced to come up with new or significantly improved goods, services as well as organizational and marketing practices. However, countries, firms and policy makers are facing great environmental challenges for sustainable development and entrepreneurship, which create large demand for Eco-innovations with environmental benefits nowadays. For these reasons, we are analyzing different factors influencing creation of firms´ Eco-innovations in the EU. To obtain an interpretable model of firms´ Eco-innovations and their determinants, we use fuzzy rule-based classification models and latest available data form Community Innovation Survey 2012-2014 created by Eurostat. Our results show that firms´ Eco-innovations are influenced by different factors according to the nature of innovation (product, process, organizational, marketing) in the EU. Public financial subsidies and firms´ environment (e.g. existing environmental regulations, taxes, charges or fees, market demand, and costs of inputs) play key role in the process of creation Eco-innovation with environmental benefits. These results show possible ways how support sustainable entrepreneurship and regional (national) development not only within analyzed countries. We provide initial analysis dealing with different kinds of Eco-innovations and its determinants that could help firms to develop and enhance their corporate innovation and environmental policies. These results could also inspire policy makers at different levels because we propose some practical implications. Keywords: eco-innovations, sustainable development, environmental benefits, entrepreneurship